2019
DOI: 10.1186/s13287-019-1310-1
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of adipose-derived mesenchymal stem cell-based therapies in liver diseases

Abstract: The liver, the largest organ with multiple synthetic and secretory functions in mammals, consists of hepatocytes, cholangiocytes, hepatic stellate cells (HSCs), sinusoidal endothelial cells, Kupffer cells (KCs), and immune cells, among others. Various causative factors, including viral infection, toxins, autoimmune defects, and genetic disorders, can impair liver function and result in chronic liver disease or acute liver failure. Mesenchymal stem cells (MSCs) from various tissues have emerged as a potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 109 publications
1
42
0
2
Order By: Relevance
“…Previous studies have indicated that BM SEPCs drove the liver regeneration process. These BM SEPCs repaired lost or injured LSECs, leading to engraftment of a substantial number of BM SEPCs and BM-derived LSECs after injury or partial hepatectomy 11,13 . Recruitment of BM SEPCs to the liver occurred through activated signaling of VEGF-sdf1 and BM SEPCs provided most of the increase in LSEC-related HGF after injury, which further promoted hepatocyte proliferation and normal liver regeneration 8,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that BM SEPCs drove the liver regeneration process. These BM SEPCs repaired lost or injured LSECs, leading to engraftment of a substantial number of BM SEPCs and BM-derived LSECs after injury or partial hepatectomy 11,13 . Recruitment of BM SEPCs to the liver occurred through activated signaling of VEGF-sdf1 and BM SEPCs provided most of the increase in LSEC-related HGF after injury, which further promoted hepatocyte proliferation and normal liver regeneration 8,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous of studies regarding liver regeneration have indicated that bone marrow (BM)-derived sinusoidal endothelial cell progenitor cells (BM SEPCs) drove the liver regeneration process. These BM SEPCs repaired lost or injured liver sinusoidal endothelial cells (LSECs), leading to engraftment of a substantial number of SEPCs and BM-derived LSECs through signaling by VEGF-stromal cell derived factor 1 (sdf1) after injury or partial hepatectomy [11][12][13][14][15] . The VEGF also stimulated increased HGF expression in the cells of the LSEC fraction, i.e., mature LSECs and/or SEPCs 12 .…”
Section: Introductionmentioning
confidence: 99%
“…With the above characteristics, MSCs are commonly used in cell therapy for regenerative medicine and immunotherapy (Squillaro et al, 2016;Galipeau and Sensebe, 2018). MSCT has caused increasing attention and is regarded as a potential new therapy for a variety of human diseases associated with brain, liver, kidney, bone, and so on (Hu et al, 2018;Chakari-Khiavi et al, 2019;Hu et al, 2019;Missoum, 2020). However, the direct use of MSCs for treating diseases encounters some problems.…”
Section: Mesenchymal Stem Cells (Mscs) and Mscs-derived Ev (Mscs-ev) mentioning
confidence: 99%
“…However, there is a shortage of suitable donor organs, and researchers are working on cell therapies in order to temporarily improve the liver's function, enabling the patient to survive longer time periods before transplantation with the final goal to replace liver transplantation altogether. The first completed trials which all employed some kind of MSC obtained, e.g., from autologous fat tissue or BM indicate an overall safety of the procedure with limited success (Hu et al 2019).…”
Section: Liver Diseasesmentioning
confidence: 99%